2022
DOI: 10.1186/s12913-022-08787-5
|View full text |Cite
|
Sign up to set email alerts
|

At-home blood self-sampling in rheumatology: a qualitative study with patients and health care professionals

Abstract: Background The goal of the study was to investigate patients’ with systemic rheumatic diseases and healthcare professionals’ experiences and preferences regarding self-sampling of capillary blood in rheumatology care. Methods Patients performed a supervised and consecutive unsupervised capillary blood self-collection using an upper arm based device. Subsequently, patients (n = 15) and their attending health care professionals (n = 5) participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Due to the nature and heterogeneity of the literature on clinical visit frequency, most if not all of the included studies reported study visit frequency as a secondary outcome. Not being the main focus of their respective reports, data on visit frequency tended to lack details, such as precise provider types (including advanced practice providers), measurements of statistical variance, disease severity, settings, and context such as clinical visits versus laboratory visits, although the latter may diminish in the future with the emergence of novel care models such as at-home blood sampling (23) and one-stop clinics (24). Future studies in rheumatology visit frequencies should strive to include many if not all of the aforementioned details to allow for a more granular understanding of the factors influencing the manner by which care is being utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nature and heterogeneity of the literature on clinical visit frequency, most if not all of the included studies reported study visit frequency as a secondary outcome. Not being the main focus of their respective reports, data on visit frequency tended to lack details, such as precise provider types (including advanced practice providers), measurements of statistical variance, disease severity, settings, and context such as clinical visits versus laboratory visits, although the latter may diminish in the future with the emergence of novel care models such as at-home blood sampling (23) and one-stop clinics (24). Future studies in rheumatology visit frequencies should strive to include many if not all of the aforementioned details to allow for a more granular understanding of the factors influencing the manner by which care is being utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Also the usage of more user-friendly devices for self-administered capillary blood collection like the TASSO-SST device could lead to a higher response rate [ 17 ]. Muehlensiepen et al interviewed rheumatic patients and health care professionals about possible at-home blood self-sampling using an upper-arm device like TASSO-SST to draw blood themselves [ 26 ]. Patients reported an easy application and high usability.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, pain or fatigue is highly sensitive to influences like depression or fibromyalgia [ 40 ]. Home blood sampling may enhance specificity, but it involves organizational challenges and remains invasive [ 17 ]. Other sensor technologies will likely emerge, such as non-invasive CRP determination or thermal cameras.…”
Section: Clinical Predictionsmentioning
confidence: 99%
“…We are amassing an overwhelming amount of data from our patients, beyond human capacity to manage. This is evident in the expanding array of digital clinical outcome assessments, digital biomarkers, or -omics data, which are now being collected through self-sampling from home along with different imaging modalities that increasingly include photos and videos by patients and doctors [ 17 ]. Machine learning allows us to build models to learn from previous data in order to deliver predictions or image recognition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%